Management of Colostomies in Infancy - Khan, Kifayat; Younas, Muhammad; Waheed, Tariq (Journal of Postgraduate Medical Institute, 2011)
The aim of the study was to assess the complications of colostomies and sort out the measures for the prevention of various complication.